Navigating Arm Robot Motion with Vision via Image Processing - Risma, Pola; Dewi, Tresna; Anggraini, Citra; Nawawi, Muhammad; Oktarina, Yurni (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The integration of vision-based technology in daily life has been perceived in recent years. The wide range of robot implementations, including agriculture, necessitates the installation of the eye to fully function and substitute the human eye. Camera and image processing work hand in hand in realizing the idea of automatic labor in daily life. This paper presents an arm robot navigated by image processing inputs from objects' coordinate positions. The robot is assigned to pick and place red tomatoes within different lighting and positions. The robot can sort the red tomatoes and ignore the green tomatoes. Inverse kinematics analysis is included to show the effectiveness of the proposed method. This robot is ideal for agricultural settings to sort the harvested fruit.